2015
DOI: 10.7314/apjcp.2014.15.24.10927
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cancer Awareness among Older Adult Individuals in Jordan

Abstract: Background: Older age is associated with an increase in the incidence of cancer cases. Diagnosis and treatment of cancer in older adults can be stressful because of health decline related to age, comorbidities and inadequate treatment for pain and other symptoms of the disease. This survey is one of the unique studies in Jordan and in the Arab world that aimed at exploring the predictors of older adult individuals awareness towards cancer. Materials and Methods: A stratified random sampling technique was follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The low knowledge was not significantly associated with the participant's sex. These results are consistent with the results of Omran et al (2015) and Ahmad and Al-Gamal (2014) which showed a low awareness level about CRC in Jordan and a need for public education about CRC risk factors, signs and symptoms. In that study, only 22 % of participants correctly ranked CRC as the commonest cause of cancer related deaths in Jordan.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The low knowledge was not significantly associated with the participant's sex. These results are consistent with the results of Omran et al (2015) and Ahmad and Al-Gamal (2014) which showed a low awareness level about CRC in Jordan and a need for public education about CRC risk factors, signs and symptoms. In that study, only 22 % of participants correctly ranked CRC as the commonest cause of cancer related deaths in Jordan.…”
Section: Discussionsupporting
confidence: 91%
“…Only 27% correctly judged their life time risk while 5% overestimated their risk. In a study by Ahmad and Al-Gamal (2014) that assessed the older Jordanians knowledge about cancer, it was found that the belief of having no health problem made the participants feel safe and not at risk of getting cancer and that was the major reason for not doing routine health check-up.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike vasculature within the blood-brain diffusion barrier, the area postrema is highly vascularized with fenestrated blood vessels, which lack tight junctions between capillary endothelial cells. The CTZ is anatomically specialized to readily sample elements present in the circulating blood and cerebrospinal fluid [15,16] .…”
Section: Designing a Norm-referenced Measuresmentioning
confidence: 99%
“…Explicating the objectives: The second step in developing a tool is explicating the objective. The behavioral objectives of the tool are stated by using Tyler and Kibler's approach, where the objective is composed of three components: (1) a description of the respondents; (2) delineation of the kind of behavior the respondent will exhibit to demonstrate accomplishment of the objective; and (3) a statement of the kind of content to which behavior relates [16,17] . The objective of this tool is to measure three kinds of nausea and vomiting (anticipatory, acute, and delayed) for patients with cancer receiving chemotherapy.…”
Section: Designing a Norm-referenced Measuresmentioning
confidence: 99%
See 1 more Smart Citation